Efeitos do modelador nasoalveolar (NAM) associado ou não à queiloplastia em indivíduos com fissura labiopalatina: ensaio clínico e revisão sistemática de literatura - Tânia Mara de Souza (2024)
Cleft lip and palate occur due to a failure in embryonic fusion. The nasoalveolar molding (NAM) is an orthopedic intervention prior to lip surgery. The objectives of this study are: to evaluate the effect of NAM on facial symmetry/maxillary arch and its psychosocial impact. To conduct a systematic review to investigate the impact of NAM on nasal symmetry. The methodology used was to evaluate 2 groups (26 babies treated with NAM and 12 babies not treated with NAM) in two time points; before NAM (T1) and after NAM (T2). The following were analyzed: maxillary arch perimeter (AP), maxillary arch length (AL) and labial frenum angle (LFA), nasal width (NW), buccal width (BW), columella angle (CA) and nostril area (NA). These same 2 groups were compared before NAM and after cheiloplasty. The impact of the cleft condition on the baby's family routine was also evaluated. Electronic searches were also performed considering studies that compared individuals undergoing cheiloplasty/NAM and individuals undergoing only cheiloplasty. Meta-analyses, assessment of risk of bias and strength of evidence were performed. The results showed that there was an increase in AP and AC in the NAM and Control groups in the T2 period compared to T1. LFA was reduced in the NAM group compared to the NAM-T1 and Control-T2 periods. NAM produced a reduction in LN in the T2 period compared to T1. CA was improved after the use of NAM in T2. NA was reduced in the NAM group in T2 compared to the Control. The NAM group showed a reduction in nasal width after NAM and cheiloplasty. The width of the mouth and the angle of the columella showed changes in the NAM group in the postoperative period. There was a reduction in the area of the cleft nostril after NAM. The global FIS scores were higher in T1 than in T2, configuring a positive impact of the use of NAM on families. In the electronic searches, 416 articles were retrieved and nine were included. In the NAM group, there was an increase in nostril height and columella width and length. Nostril width and bialar width decreased in the short term and increased in the long term in individuals undergoing cheiloplasty and NAM. Six studies showed a moderate risk of bias; three showed a serious risk of bias. The strength of evidence ranged from very low to moderate. Thus, we were able to conclude that NAM treatment improved LFA, NW and CA measurements, improving maxillary and nasal symmetry. NAM promoted an increase in the columella angle and a reduction in the widths of the mouth and nose, and also a reduction in the area of the nostril affected by the cleft. NAM showed a positive impact on family emotions. Nostril height and columellar width/length were favored by cheiloplasty followed by NAM. Alar length was positively impacted by NAM.